The Implications of a System-Wide Positive Behavioral Intervention Initiative: From Design to Successful Implementation - Austin, Vance L.; Malow, Micheline S.; Josephs, Nikki L.; Ecker, Andrew J. (Journal of the American Academy of Special Education Professionals, 2016)
Residential schools for students with emotional and behavioral disorders have been steadily evolving since the beginning of the 20th Century. Traditional behavioral approaches involving physical restraint and confinement have been replaced with more humanistic interventions involving positive reinforcement. This article traces this transformative journey from the punitive techniques employed in the 1950s and 1960s through to the present and the use of prosocial interventions recommended in current best practices such as PBIS. The authors share the success story of one such residential school as it embraced a sea change in behavior management philosophy, moving from a more traditional behaviorist model to a positive behavior intervention and support system (PBIS) dubbed: "WISE."